Decidual Natural Killer Cells: A Good Nanny at the Maternal-Fetal Interface During Early Pregnancy - Liu, Yuefang; Gao, Shujun; Zhao, Yangjing; Wang, Hui; Pan, Qiong; Shao, Qixiang (Frontiers in Immunology, 2021)
Decidual natural killer (dNK) cells are the tissue-resident and major subpopulation of NK cells at the maternal-fetal interface. It has been demonstrated that dNK cells play pivotal roles in pregnancy, including keeping maternal-fetal immune tolerance, promoting extravillous trophoblast (EVT) cell invasion, and driving uterine spiral artery remodeling. However, the molecular mechanisms haven’t been elucidated until recent years. In this review, we systemically introduce the generation, subsets, and surface or soluble molecules of dNK cells, which are critical for maintaining the functions of dNK cells. Further, new functions of dNK cells including well-controlled cytotoxicity, immunosurveillance and immunotrophism supporting via the cell-cell interaction between dNK cells and EVT cells are mainly focused. The molecular mechanisms involved in these functions are also illustrated. Moreover, pregnancy-associated diseases caused by the dNK cells abnormalities are discussed. It will be important for future investigations about the mechanism of maintenance of pregnancy and parturition and potential clinical applications of dNK cells.